KOMPARASI ALGORITMA LOGISTIC REGRESSION DAN NAIVE BAYES UNTUK MENYELEKSI MELAMAR PEKERJAAN PERUSAHAAN BESAR BAGI ALUMNI SMK - Ria indah fitria; Nur Tulus Ujianto (Engineering : Jurnal Bidang Teknik, 2021)
Vocational High School is one of the levels of secondary education with specialization preparing graduates to be ready to work. Vocational education has varied meanings but can be seen as a red thread. There are a lot of alumni from Vocational Schools who after they graduate want jobs in large companies so they can get a fairly large salary. Large companies have several criteria in finding employees. Not all large companies can accept alumni fromSMK so easily. Large companies have several requirements in selecting or selecting employees, eg 1) have good grades in subjects, 2) skills in engineering, 3) skills in communication, and 4) in attitude must have good atitude. Therefore the Vocational School students are trained to be ready to work with good skills and good atitude. In this study, the proposed method used is the Naive Bayes Aggression and logistic regression.